By-Products: Characterisation and Use as Food (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
There is an increased need to design circular economy models to make our food system more sustainable. This book brings together a review, a short communication, and several research articles showcasing a range of circular economy initiatives: some that valorise and characterise by-products using different technologies, others that apply by-products to new upcycled food products, and finishing with one article investigating consumer attitudes towards a food that comes from a circular economy initiative. This book highlights the diversity of expertise needed to valorise by-products from farm to fork and presents different by-products, technologies, and potential applications.